Coping strategies among resident physicians in Brazil: an assessment on the role of psychological distress - Giulia Campos Lage; Vinicius Sousa Pietra Pedroso (Jornal Brasileiro de Psiquiatria)
ABSTRACT Introduction Residency is a unique period in medical professional training, characterized by an imbalance between technical training and care requirements. Evidences have been showing that the rates of problems related to Mental Health are significant in this population and deserve attention. Methods In this work, specific instruments (DASS-21 and Coping Strategies Inventory ) were used to assess symptoms related to depression, anxiety and stress, as well as coping strategies, among residents enrolled in programs at Fundação Hospital do Estado de Minas Gerais between 2021 and 2023. Results 116 residents completed the assessment. The prevalence of depression reached 51.3% of the sample; anxiety 36.7%; and stress 56.5%. The presence of depressive, anxious or stress symptoms was correlated with the perception of worse sleep quality. Residents with depressive symptoms tended to adopt certain coping styles (confrontation, avoidance, escape and avoidance and positive reappraisal) differently from those without depression, as well as residents with anxiety or stress-related symptoms showed coping styles significantly different from those without symptoms. (confrontation, avoidance, acceptance of responsibility and escape and avoidance). Conclusions A high prevalence of psychiatric symptoms was observed among residents, which correlated with poor sleep quality and specific coping strategies. These data can contribute to a better understanding of the phenomenon of mental illness among residents and to the creation of risk screening strategies, interventions and mental health promotion in medical residency programs.